Influence of seasonality on excursion demand: statistical approach - Liudmyla Hutsal; Valentyna Stoliar (Journal of Education, Health and Sport)
Studying the effect of seasonality on excursion demand is an important aspect in the management of the tourist business. Seasonal fluctuations in demand for excursion services reflect the changing preferences of tourists throughout the year and are determined by factors such as weather, cultural events, holiday periods and destination characteristics. The purpose of the article is to analyze seasonal trends in excursion demand based on statistical methods, which allows identifying patterns in consumer behavior and adapting the offers of tour operators to improve business efficiency.